Atmospheric pressure plasma jet for respiratory face masks decontamination and re-use: Considerations on microbiological efficacy, material impact and product lifecycle. - Diletta Scaccabarozzi; Jessica Ponti; Sabrina Gioria; Dora Mehn; Taija Sinkko; Fulvio Ardente; Francesco Fumagalli (PLoS ONE)
Disposable filtering face piece respirators (FFRs) are not approved for reuse as standard of care. However, lessons learnt from the SARS-CoV-2 pandemic, FFRs decontamination and reuse may be needed as crisis capacity strategy to ensure availability in medical facilities. We studied a decontamination methodology based on atmospheric pressure plasma technology, which allows for rapid, contact-free decontamination without utilisation of harmful chemicals, and suitable to access small pores and microscopic filters openings. Promising performances in terms of bioburden reduction (Log6) were achieved while imparting mainly transient chemical surface modifications to the masks filtering layers. The plasma decontamination process proposed was also considered in terms of the environmental impact of re-use technology for FFR medical devices in order to understand its sustainability. This study assessed the feasibility of an atmospheric pressure plasma approach for the decontamination of disposable filtering face piece respirators (FFR) or respiratory masks commonly used in hospital settings.